Linking Business Ecosystems and Transaction Cost Theory: Between Market and Hierarchy and the Role of Power - Claude Meier; Urs Jäckli (International School for Social and Business Studies, 2023)
Purpose: Business ecosystems substitute more and more the idea of linear value chains as a conceptual idea of economic value creation. There are two conditions to make sense to establish an ecosystem. Firstly, complementarity: the complements of the actors have to be compatible with each other. Secondly, there must be a need for coordination between the economic actors. This is given if the complements have a certain minimum degree of specificity, i.e. if they aren't generic. Specificity provides the link to the transaction cost theory, which knows two extreme forms of coordination: market and hierarchy. In this article we argue why ecosystems are to be placed between the two. Moreover, we consider dominance in ecosystems and the transition to oligopolistic situations. Oligopolies hamper the functioning of ecosystems. The purpose of this article is to provide a clear conceptual view on ecosystems by linking different theories. Study design/methodology/approach: The study design is conceptual. By linking conceptual considerations about business ecosystems to transaction cost theory their basic analytical categories can be elaborated and considered more focussed. The conceptual clarification leads to new and deeper questions. Findings: A main finding is the quite clear elaboration of complementarity and the need for coordination as the basic preconditions for business ecosystems to make sense as a form for creating economic value. Moreover, it was shown that oligopolies can hamper the advantages and the function of ecosystems. Originality/value: The main value is the provision of a clear and overall precise view on ecosystems. The originality lies in clearly showing the basic analytical categories. This provides a clear picture of the basic structure of ecosystems.